RELATIONSHIP OF STRESS LEVEL AND SLEEP QUALITY IN NEW STUDENTS IN D3 STUDENTS OF JEMBER UNIVERSITY, PASURUAN CITY CAMPUS - Evy Aristawati; R.A. Helda Puspitasari (UPT Penerbitan Universitas Jember, 2020)
A new student or better known as new student is someone who has just entered the stage / process of gaining knowledge or learning and administratively has just been recorded as having attended a university (Hartaji, 2012). The large number of activities during the initial period of lectures that must be completed triggers new students to pressure themselves to be able to carry out activities properly to fulfill the assigned tasks within 24 hours. This phenomenon causes new students to experience fatigue and the risk of experiencing stress, which affects the quality of their sleep. The purpose of this study was to determine the relationship between stress levels and sleep quality in new students of the D3 study program, Jember University, Pasuruan City Campus. This research design used cross sectional method. The population of this study was 107 people with a sample of 107 people who were taken by total sampling. Statistical test using the Sperman Rank test. The results showed that the stress level of new students was a mild stress level of 52 people (48.4%). The sleep quality of new students was poor sleep quality as many as 54 people (50%). Based on statistical tests, the results obtained p value 0.012 <α 0.05 with a correlation coefficient of 0.226, which means that there is a weak positive relationship between stress levels and sleep quality in new students of D3 study program, Jember University, Pasuruan City Campus. This result was possible because during this pandemic, students had to undergo new learning methods for them, namely online learning models that required them to master IT well. In addition, the number of assignments given by lecturers online takes a lot of time to complete, so that it affects the quality of student sleep. So, the role of nurses as counselors and educators is needed to provide counseling and education about stress management and sleep needs management for new students of the D3 study program, Jember University, Pasuruan City Campus. Keywords: Stress Level, Sleep Quality, new students